Iridium(III)‐Catalyzed Regioselective Carbenoid Insertion C–H Alkylation by α‐Diazotized Meldrum's Acid. Issue 34 (11th November 2016) - Lv, Honggui; Xu, William L.; Lin, Kunhua; Shi, Jingjing; Yi, Wei
Abstract : A practical and straightforward protocol for Ir III ‐catalyzed regioselective carbenoid insertion C–H alkylation mediated by α‐diazotized Meldrum's acid was developed. The assistance of external additives and oxidants was not needed, and the developed Ir III catalysis proceeds in a highly efficient manner (e.g., mild reaction conditions, short reaction times and excellent regioselectivity) and demonstrates good compatibility with several privileged substrates, such as valuable N ‐(2‐pyrimidyl)indoles, phenylpyridines, and the marketed drug edaravone and its analogues, and thus provides a good complement to previous methods for the rapid construction of the corresponding alkylated products. Abstract : A simple protocol for Ir III ‐catalyzed carbenoid insertion C–H alkylation mediated by α‐diazotized Meldrum's acid is developed. The reaction proceeds in a highly efficient manner and demonstrates good compatibility with several privileged substrates and, thus, provides a good complement to other methods for the rapid construction of the corresponding alkylated products.